Assistance for Student Entrepreneurial Character Development through Compost Fertilizer Production Activities from Household Waste - Riyansyah, Ahmad; Owoyemi, Abiodun Ezekiel; Laksito, Grida Saktian; Yurechko, Mariyan (Research Collaboration Community (Rescollacom), 2023)
Socialization activities on composting practices by utilizing household waste as an effort to take advantage of potential and protect the surrounding environment. This activity was carried out at Junior High School 2 Jatinangorwith the aim of creating a mindset for productive behavior and an entrepreneurial spirit from the production of compost which has high economic value. The method of implementing community service activities is carried out with training that produces skills, lecture methods, questions and answers, discussions, simulations and mentoring. The results of the activity revealed that the implementation of this composting activity was recognized by some students as an easy, simple, and beneficial practice for greening the environment. Socialization of making compost provides great benefits, namely an increase in students' knowledge about the benefits of organic waste residue as raw material for making compost. With this activity it is hoped that the impact will affect students' desire to always protect the environment and be able to apply it at home and in the environment around where they live in stages.